Renal involvement in eosinophilic granulomatosis with polyangiitis - Reggiani, Francesco; L’Imperio, Vincenzo; Calatroni, Marta; Pagni, Fabio; Sinico, Renato Alberto (Frontiers in Medicine, 2023)
Eosinophilic granulomatosis with polyangii3s (EGPA) is a necro3zing vasculi3s, which typically affects small-to medium-sized blood vessels. It is characterized by the presence of 3ssue infiltrates rich in eosinophils, along with the forma3on of granulomatous lesions. About 40% of cases have posi3ve an3-neutrophil cytoplasm an3bodies (ANCA), with predominant perinuclear staining, and an3myeloperoxidase (an3-MPO) specificity in about 65% of cases. Typical manifesta3ons of EGPA include the late onset of asthma, nasal and sinus-related symptoms, peripheral neuropathy, and significant eosinophilia observed in the peripheral blood. In contrast to granulomatosis with polyangii3s and microscopic polyangii3s, renal involvement in EGPA is less frequent (about 25%) and poorly studied. Necro3zing pauci-immune crescen3c glomerulonephri3s is the most common renal presenta3on in pa3ents with ANCA-posi3ve EGPA. Although rarely, other forms of renal involvement may also be observed, such as eosinophilic inters33al nephri3s, mesangial glomerulonephri3s, membranous nephropathy, or focal sclerosis. A standardized treatment for EGPA with renal involvement has not been defined, however the survival and the renal outcomes are usually beRer than in the other ANCA-associated vasculi3des. Nonetheless, kidney disease is an adverse prognos3c factor for EGPA pa3ents. Larger studies are required to beRer describe the renal involvement, in par3cular for paRerns different from crescen3c glomerulonephri3s, and to favor the development of a consensual therapeu3c approach. In this ar3cle, in addi3on to personal data, we will review recent findings on pa3ent clinical phenotypes based on ANCA, gene3cs and the impact of biological drugs on disease management.